(untitled) (Journal of Engineering, 2024)
This paper presents a techno-economic evaluation of a Hybrid Renewable Energy System (HRES) for the University of Baghdad College of Engineering. The objectives include improving reliability and mitigating grid demand. The design of a customized grid-connected HRES for the university, incorporating solar PV and a diesel generator (DG). The optimal hybrid configuration is determined through a complete assessment of economic, technical, and environmental factors using Homer-Pro software. Besides it addresses critical challenges in provides valuable insights into sustainable energy solutions for educational institutions. Additionally, the study extends its scope by presenting a comprehensive analysis of four different proposed hybrid energy systems. The College of Engineering is anticipated to have an estimated daily load of 1110.48 kWh and a peak load of 494.56 kW. The optimal cost for a system comprising PV, DG, and grid is determined to be net present cost (NPC) is 288,348,027IQD and levelized cost of energy (LCOE) is 57.2896IQD/kWh. The analysis emphasizes the integration of both renewable and conventional sources to create a sustainable and efficient energy solution.